About manifestation of the piezojunction effect in diode temperature sensors - Borblik, V.L.; Shwarts, Yu.M.; Venger, E.F. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2003)
An analytical theory of piezojunction effect has developed in application to silicon diode temperature n+-p type sensors, which for the first time takes into account three-subbands structure of the valence band of silicon. The compressive and tensile stresses (along the main crystallographic directions), long- and short-base diodes, longitudinal and transverse effects have been considered.
It is shown that the three-subbands model results in even more nonlinear dependence of changes in the sensor readings on stress value (in comparison with the two-subbands model), holds minimality of the longitudinal piezojunction effect under stress orientation along the [100] direction and predicts substantially larger effect value for the strain perpendicular to the current through the diode.